Potassium phosphIte increases tolerance to UV-B in potato - Oyarburo, Natalia Soledad (2015)
The use of biocompatible chemical compounds that enhance plant disease resistance through Induced Resistance (IR) is an innovative strategy to improve the yield and quality of crops. Phosphites (Phi), inorganic salts of phosphorous acid, are environment friendly, and have been described to induce disease control. Phi, similar to other plant inductors, are thought to be effective against different types of biotic and abiotic stress, and it is assumed that the underlying signaling pathways probably overlap and interact. The signaling pathways triggered by UV-B radiation, for instance, are known to crosstalk with other signaling routes that respond that biotic stress. In the present work, the effect of potassium phosphite (KPhi) pre-treatment on UV-B stress tolerance was evaluated in potato leaves. Plants were treated with KPhi and, after 3 days, exposed to 2 h/day of UV-B (1.5 Watt m−2) for 0, 3 and 6 days. KPhi pre-treatment had a beneficial effect on two photosynthetic parameters, specifically chlorophyll content and expression of the psbA gene. Oxidative stress caused by UV-B was also prevented by KPhi. A decrease in the accumulation of hydrogen peroxide (H2O2) in leaves and an increase in guaiacol peroxidase (POD) and superoxide dismutase (SOD) activities were also observed. In addition, the expression levels of a gene involved in flavonoid synthesis increased in UV-B-stressed plants only when pre-treated with KPhi. Finally, accumulation of glucanases and chitinases was induced by UV-B stress and markedly potentiated by KPhi pre-treatment. Altogether, this is the first report that shows a contribution of KPhi in UV-B stress tolerance in potato plants.